Pharmacokinetics of eperisone following oral administration in healthy Korean volunteers. (3rd March 2021) - Baek, In‐hwan; Back, Hyun‐moon; Chae, Jung‐woo; Ha, Eun‐Sol; Park, Heejun; Choi, Du Hyung; Staatz, Christine E.; Kim, Min‐Soo
Abstract: Eperisone is an oral muscle relaxant used to treat musculoskeletal diseases, which exhibits high pharmacokinetic (PK) variability in bioequivalence studies. The aim of this study was to characterize the PKs of eperisone following its oral administration to Korean volunteers through the conduct of a noncompartmental and population analysis. A total of 360 concentration‐time measurements collected on two separate occasions from 15 healthy volunteers during a bioequivalent study of eperisone 50 mg (Murex ® ) were used in the PK analysis. Noncompartmental analysis was performed using WinNonLin TM and population analysis was performed using NONMEM ® . The possible influence of thirty demographic and pathophysiological characteristics on the PKs of eperisone were explored. Based on noncompartmental analysis mean eperisone elimination half‐life, apparent clearance ( CL / F ), and apparent volume of distribution were estimated to be 3.81 h, 39.24 × 10 3  l/h × 10 3  L, respectively. During population PK modeling a two‐compartment model with first‐order absorption rate constant (typical population K a  = 1.5 h −1 ) and first‐order elimination (typical population CL / F and apparent volume of distribution in the central compartment [ V c / F ] = 30.8 × 10 3  l/h and 86.2 × 10 3  l, respectively) best described the PKs of eperisone. Interindividual variability in CL / F and V c / F were estimated to be 87.9% and 130.3%, respectively and interoccasion variability in CL / F and V c / F were estimated to be 23.8% and 30.8%, respectively. Aspartate aminotransferase level and smoking status were identified as potential covariates that may influence the CL / F of eperisone. This is the first study to develop a disposition model for eperisone and investigate the potential influence of covariate factors on it PK variability. Abstract :